2017
DOI: 10.1186/s41747-017-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of aquaporins and apparent diffusion coefficient from ultra-high b-values in a rat model of diabetic nephropathy

Abstract: BackgroundTo assess kidney damage in a rat model of type-2 diabetic nephropathy based on apparent diffusion coefficient (ADC) data obtained from ultra-high b-values and discuss its relationship to the expression of aquaporins (AQPs).MethodsThis study was approved by the institutional Animal Care and Use Committee. Thirty male Sprague-Dawley rats were randomised into two groups: (1) untreated controls and (2) diabetes mellitus (DM). All rats underwent diffusion-weighted imaging (DWI) with 18 b-values (0–4500 s/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…When the b -value is greater than 2,000 s/mm 2 , it is most likely to reflect the effect of Aquaporin-4 on water transport ( Zeng et al, 2018 ). According to previous studies ( Xueying et al, 2015 ; Hu et al, 2017 ; Wang et al, 2017 ; Xue et al, 2019 ), ADC mh may be associated with water transportation by aquaporins. We, therefore, speculated whether the large value on ADC mh represents the high expression of AQP4 which plays a crucial role in cerebral ischemia.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…When the b -value is greater than 2,000 s/mm 2 , it is most likely to reflect the effect of Aquaporin-4 on water transport ( Zeng et al, 2018 ). According to previous studies ( Xueying et al, 2015 ; Hu et al, 2017 ; Wang et al, 2017 ; Xue et al, 2019 ), ADC mh may be associated with water transportation by aquaporins. We, therefore, speculated whether the large value on ADC mh represents the high expression of AQP4 which plays a crucial role in cerebral ischemia.…”
Section: Discussionmentioning
confidence: 81%
“…Multi-high b -value ADCs from multi-high- b values has been proved to be a useful parameter for evaluating brain damage in Parkinson’s disease ( Xueying et al, 2015 ), glioma grading ( Hu et al, 2017 ; Tan et al, 2018 ), early detection of kidney damage in diabetic nephropathy ( Wang et al, 2017 ), and monitoring the pathophysiological changes of AD ( Xue et al, 2019 ). In our study, multi-high b -value ADC was applied to a focal cerebral ischemia rat model.…”
Section: Discussionmentioning
confidence: 99%
“…With the knowledge of slower water transportation speed ( 36 ) resulted from the AQPs, previous studies indicated that ADC derived in the high- b value range might be one potential marker for AQPs expressions in gliomas ( 5 ) or other diseases ( 25 , 37 ). However, our results showed that the ADC uh was not completely independent from other DWI metrics such as ADC st to independently indicate AQPs expression.…”
Section: Discussionmentioning
confidence: 99%
“…When room temperature was reached, incubation of slides with 1% bovine serum albumin (BSA) for 1 h was done and then incubation with primary antibodies overnight at 4 °C was performed. Three primary antibodies were used in this study: 1-rabbit polyclonal primary antibodies raised against aquaporin-1 (AQP1) (GB11311-1, Servicebio, China at 1:1000 dilution); 2-rabbit polyclonal primary antibodies raised against aquaporin-4 (AQP4) (GB11529, Servicebio, China at 1:1200 dilution) for assessment of their role in diabetes and intermittent fasting [89]; and 3-rabbit polyclonal primary antibodies raised against microtubule-associated proteins 1A/1B light chain 3B (MAP1LC3-II) (YPA1652, Chongqing Biospes, China at 1:200 dilution) for assessment of autophagy [90]. The sections were then rinsed with PBS followed by these three steps: Step 1, incubation with horseradish peroxidase (HRP) conjugated secondary antibodies for 0.5 h at 37 °C; Step 2, incubation with labelled streptavidin-biotin for 0.5 h at 37 °C; and…”
Section: Immunohistochemical Study and Morphometric Analysismentioning
confidence: 99%